(untitled) (Research, Society and Development, 2021)
Introduction: Psychosomatics is a science that comprehends the human being in an integral way, without separating mind and body, in which the process of illness and health is understood based on biopsychosocial aspects. Objectives: to characterize in the scientific literature in which situations of illness the psychosomatic approach is adopted; describe the approaches used for the purpose of psychosomatic interventions and analyze the results of the interventions through non-invasive body therapeutic modalities. Methodology: The present study was based on the Scoping Review method. The search was carried out using LILACS, Scopus, Web of Science and PubMed databases. 430 articles were found, of which, after applying the criteria for inclusion and removal of duplicates, 14 publications were included in the review. Results: the psychosomatic approach is generally used in complex and chronic illness situations, sensory and emotional conditions, and also for health promotion. Most of these approaches are used in conjunction with other therapies. The results of the interventions are generally presented in a quantitative way using a wide range of statistical analyzes. Conclusion: The psychosomatic approach is adopted in the literature in situations of chronic illness, complex diseases, but also in the prevention and promotion of health. There is a need for more qualitative studies to assess the individual’s subjective issues.